2004
DOI: 10.1007/s00330-004-2364-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined small and large bowel MR imaging in patients with Crohn?s disease: a feasibility study

Abstract: MRI of the small bowel is a new method for the assessment of inflammatory bowel diseases. However, inflammatory bowel disease can affect both the small and large bowel. Therefore, our goal was to assess the feasibility of displaying the small bowel and colon simultaneously by MR imaging. Eighteen patients with inflammatory bowel disease were studied. For small bowel distension, patients ingested a solution containing mannitol and locust bean gum. Furthermore, the colon was rectally filled with water. MR examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 22 publications
4
45
0
1
Order By: Relevance
“…Technical progress in MR imaging has formed the basis for a rapid evaluation of the GI tract with improved image quality (15)(16)(17). The benefits of 3D T1W gradient echo technique utilizing ultrashort TE and TR include minimization of artifacts from susceptibility effects that arise from bowel gas and improved spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Technical progress in MR imaging has formed the basis for a rapid evaluation of the GI tract with improved image quality (15)(16)(17). The benefits of 3D T1W gradient echo technique utilizing ultrashort TE and TR include minimization of artifacts from susceptibility effects that arise from bowel gas and improved spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in appraising these aspects contributed to the low interobserver values since, in addition to mesenteric hypervascularization, enhancement of bowel segments was rated differently by the two observers in 75 of 151 assessable segments. In the literature contrast enhancement has been described as one of the most important parameters that indicate active disease (9,27,29). However, in these studies quantitative measurements of percentage of contrast enhancement were obtained only from the most diseased segment of bowel, and were subsequently correlated with endoscopic findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, before MRI can be considered an alternative for endoscopy in CD, it should be firmly established that in addition to detecting disease activity, MRI is capable of revealing both the severity and the exact location of disease. A few prospective studies have compared MRI with endoscopy regarding the severity of disease, but only the five most recent of these studies also analyzed the accuracy of MRI for localizing disease (27)(28)(29)(30)(31)(32)(33). The results of these studies were conflicting, and the reported sensitivities and specificities varied widely from approaching endoscopic accuracy to considerable over-or underestimation of disease.…”
mentioning
confidence: 99%
“…Ascites and bowel wall edema are displayed with high signal intensity in T2-weighted images and low in T1-weighted images, which is the same as for biphasic contrast agents. While signal intensity of positive contrast agent is high in T2-and T1-weighted images, on the other hand negative contrast agents are depicted as hypointense in T2-and T1-weighted images 7 . Therefore, application of negative contrast agents is the best choice for effective visualization of the above-mentioned problem parts of the abdominal cavity.…”
Section: Introductionmentioning
confidence: 93%
“…These SPIO per-oral contrast agents enable decrease in noise and motion artifacts related to bowel peristalsis and help us to improve the detection of intramural edema and extramural complications (necrosis, fat edema, mesenterial edema, abscess formation or fistulas) (ref. 7,8 ). Ascites and bowel wall edema are displayed with high signal intensity in T2-weighted images and low in T1-weighted images, which is the same as for biphasic contrast agents.…”
Section: Introductionmentioning
confidence: 99%